If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y(y + -1) = 3 + -1y Reorder the terms: 2y(-1 + y) = 3 + -1y (-1 * 2y + y * 2y) = 3 + -1y (-2y + 2y2) = 3 + -1y Solving -2y + 2y2 = 3 + -1y Solving for variable 'y'. Reorder the terms: -3 + -2y + y + 2y2 = 3 + -1y + -3 + y Combine like terms: -2y + y = -1y -3 + -1y + 2y2 = 3 + -1y + -3 + y Reorder the terms: -3 + -1y + 2y2 = 3 + -3 + -1y + y Combine like terms: 3 + -3 = 0 -3 + -1y + 2y2 = 0 + -1y + y -3 + -1y + 2y2 = -1y + y Combine like terms: -1y + y = 0 -3 + -1y + 2y2 = 0 Factor a trinomial. (-1 + -1y)(3 + -2y) = 0Subproblem 1
Set the factor '(-1 + -1y)' equal to zero and attempt to solve: Simplifying -1 + -1y = 0 Solving -1 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1y = 0 + 1 -1y = 0 + 1 Combine like terms: 0 + 1 = 1 -1y = 1 Divide each side by '-1'. y = -1 Simplifying y = -1Subproblem 2
Set the factor '(3 + -2y)' equal to zero and attempt to solve: Simplifying 3 + -2y = 0 Solving 3 + -2y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2y = 0 + -3 -2y = 0 + -3 Combine like terms: 0 + -3 = -3 -2y = -3 Divide each side by '-2'. y = 1.5 Simplifying y = 1.5Solution
y = {-1, 1.5}
| 5(x+5)(x-10)=2(2.5x*x-1.9) | | 48=-8w | | 5(x+5)(x-10)=8.7 | | 9=2x-4 | | 5(x+5)(x-10)=12.5x-3.8 | | x-1.4=5.7 | | (x-7)(x+2)=x*x+10 | | x+2x-15=12 | | 5(-3-2x)=4 | | 4*8(x-4)=2x | | 2*8(x-4)=2x | | y=-0.02x^2+x+2 | | 2.1x-5.7=3.9(4.3-1.8x) | | 4x+2=3(x-1)+2 | | 4x-x=x+8 | | 4x+2=8x-14 | | 48-(18-58x)=28-(17+18x-57) | | 25x=22 | | 2x+1=5+x | | 0.5x-8=-3(0.5x+2) | | 12x-22=9x-29 | | x-2(x^2-4x+4)+x-2=0 | | x^2-4x+1=o | | 2(x+1)+7=2x+9 | | 7x+2=3x+1 | | 3(4)(7)= | | 2x+3-4x=7(x-5) | | 4.7(2f-0.5)=-61(1.6f-8.3f) | | 3x+6(2-x)-13= | | (x-2)(x-3)=(x+2)(x+3) | | (x-2)(x-3)=1 | | 104=0.5[(360-x)-x] |